2019
DOI: 10.3390/pr7020113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Utilization of 110 °C and 120 °C Heat Sources in a Geothermal Energy System Using Organic Rankine Cycle (ORC) with R245fa, R123, and Mixed-Ratio Fluids as Working Fluids

Abstract: Binary cycle experiment as one of the Organic Rankine Cycle (ORC) technologies has been known to provide an improved alternate scenario to utilize waste energy with low temperatures. As such, a binary geothermal power plant simulator was developed to demonstrate the geothermal energy potential in Dieng, Indonesia. To better understand the geothermal potential, the laboratory experiment to study the ORC heat source mechanism that can be set to operate at fixed temperatures of 110 • C and 120 • C is conducted. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
(48 reference statements)
0
9
0
1
Order By: Relevance
“…Aplikasi ilmu kontrol yang lebih komplek biasanya diterapkan di industri pembangkit [4,5] maupun skala laboratorium seperti yang dilakukan oleh Surindra et al [6,7]. Aplikasi dibidang perpindahan panas di heat exchanger sudah banyak dilakukan oleh Surindra [8][9][10][11][12] dalam penelitiannya di bidang ORC. Meskipun begitu pemodelan untuk memahami perpindahan panas dari sudut pandang control engineering masih sangat diperlukan untuk memberikan pemahaman didalam pembelajaran di bidang sistem pengaturan.…”
Section: Pendahuluanunclassified
“…Aplikasi ilmu kontrol yang lebih komplek biasanya diterapkan di industri pembangkit [4,5] maupun skala laboratorium seperti yang dilakukan oleh Surindra et al [6,7]. Aplikasi dibidang perpindahan panas di heat exchanger sudah banyak dilakukan oleh Surindra [8][9][10][11][12] dalam penelitiannya di bidang ORC. Meskipun begitu pemodelan untuk memahami perpindahan panas dari sudut pandang control engineering masih sangat diperlukan untuk memberikan pemahaman didalam pembelajaran di bidang sistem pengaturan.…”
Section: Pendahuluanunclassified
“…Efforts to obtain a working fluid according to the ORC system were carried out by mixing pure refrigerant R123 and R245fa. Surindra et al [9] have reported that they mix R123 and R245fa to operate the ORC system. R245fa 1:1 R123 (admixture R123 50% and 50% R245fa), R123 2:1 R245fa (admixture R123 66,6% and 33,3% R245fa) and R245fa 1:2 R123 (admixture R245fa 33,3% and 66,6% R123).…”
Section: Working Fluid Cyclementioning
confidence: 99%
“…On the other hand, through research has just been published, Prasetyo et al [7] and Sarmiento [8] revealed R123 working fluid has been adopted to produce the highest ORC efficiency and environmental performance. Furthermore, in order to find alternative working fluid which appropriate with design challenge and complicated application, Surindra et al,2019 [9] established ORCS as simulator of Organic Rankine Cycle test bench with mixed-ratio of working fluid R123, and R245fa.…”
Section: Introductionmentioning
confidence: 99%
“…Surindra, Caesarendra, Prasetyo, Mahlia, and Taufik [4] Organic Rankine cycles in geothermal energy systems.…”
Section: Energy System Designmentioning
confidence: 99%